2018
DOI: 10.1002/adem.201800779
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Process, Tensile, and Gamma Rays Shielding Properties of Newly Developed Fiber Metal Laminates Based on an Al–Li Alloy and Carbon Fibers‐Tungsten Carbide Nanoparticles Reinforced Phthalonitrile Resin Composite

Abstract: In the present study, new fiber‐metal laminates (FMLs) are manufactured from the lay‐up process of the carbon fibers‐tungsten carbide nanoparticles/phthalonitrile (CFs‐WC/PN) composite and the Al–Li alloy. The properties of the developed hybrids are analyzed and compared with those of the monolithic alloy. Generally speaking, the results indicate that the amount of the fiber considerably affects the tensile properties. The mechanical properties of the FMLs show enhancements over both the Al–Li alloy and the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The applied stress of all the Al-LiFMLs was then transferred to the alloy layers and was considerably reduced. It was deduced that during the specimen testing, the composite layers in the FMLs failed before the metal layers which supported the remaining load [3,4,33]. Figure 4(b,d) evidently showed that, during the tensile testing, the failure of composite layers first occurred, then the fracture of the Al–Li alloy happened.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The applied stress of all the Al-LiFMLs was then transferred to the alloy layers and was considerably reduced. It was deduced that during the specimen testing, the composite layers in the FMLs failed before the metal layers which supported the remaining load [3,4,33]. Figure 4(b,d) evidently showed that, during the tensile testing, the failure of composite layers first occurred, then the fracture of the Al–Li alloy happened.…”
Section: Resultsmentioning
confidence: 98%
“…Fibre-metal laminates (FMLs), as a new category of composite materials have found, in recent decades, extensive applications in various industrial fields, such as the advanced aerospace/aeronautical industry, marine, and armour sectors, due to their versatile properties such as high specific strength and specific stiffness, excellent fatigue life, corrosion resistance among other benefits [1,2]. Actually, the key feature of these advanced materials is to be comprised of thin sheets of metals stacked and adhesively bonded together with a fibre-reinforced polymeric prepreg, which is primarily governed by the attractive characteristics of these two systems [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation